Fetal and maternal outcomes of segmental uterine resection in emergency and planned placenta percreta deliveries - Şükran Doğru; Fatih Akkuş; Aslı Altinordu Atci; Ülfet Sena Metin; Mehmet Uyar; Ali acar (Korean Society of Obstetrics and Gynecology, 2024)
Objective This study evaluated maternal and fetal outcomes of emergency uterine resection versus planned segmental uterine resection in patients with placenta percreta (PPC) and placenta previa (PP). Methods Patients with PP and PPC who underwent planned or emergency segmental uterine resection were included in this study. Demographic data, hemorrhagic morbidities, intra- and postoperative complications, length of hospital stay, surgical duration, and peri- and neonatal morbidities were compared. Results A total of 141 PPC and PP cases were included in this study. Twenty-five patients (17.73%) underwent emergency uterine resection, while 116 (82.27%) underwent planned segmental uterine resections. The postoperative hemoglobin changes, operation times, total blood transfusion, bladder injury, and length of hospital stay did not differ significantly between groups (P=0.7, P=0.6, P=0.9, P=0.9, and P=0.2, respectively). Fetal weights, 5-minute Apgar scores, and neonatal intensive care unit admission rates did not differ significantly between groups. The gestational age at delivery of patients presenting with bleeding was lower than that of patients who were admitted in active labor and underwent elective surgery (32 weeks [95% confidence interval [CI], 26-37] vs. 35 weeks [95% CI, 34-35]; P=0.037). Conclusion Using a multidisciplinary approach, this study performed at a tertiary center showed that maternal and fetal morbidity and mortality did not differ significantly between emergency versus planned segmental uterine resection.